Everyday emotional intelligence : (Harvard Business Review Press, 2017)
According to research by Daniel Goleman, emotional intelligence has proved to be twice as important as other competencies such as technical skills and IQ in determining outstanding leadership. It is now one of the crucial criteria in hiring and promotion processes, performance evaluations, and professional development courses. And it's not innate--it's a skill that all of us can improve. With this double volume you'll get HBR's 10 Must Reads on Emotional Intelligence and the HBR Guide to Emotional Intelligence. That's 10 definitive HBR articles on emotional intelligence by Goleman and other leaders in the field, selected by our editors--paired with smart, focused advice from HBR experts about how to implement those ideas in your daily work life. With Everyday Emotional Intelligence, you'll learn how to: - Recognize your own EQ strengths and weaknesses - Regulate your emotions in tough situations - Manage difficult people - Build the social awareness of your team - Motivate yourself through ups and downs - Write forceful emails people won't misinterpret - Make better, less emotionally biased decisions